Sensitivity and specificity of the method used for ascertainment of healthcare-associated infections in the second Slovenian national prevalence survey - Serdt, Mojca (Zdravstveno varstvo, 2016)
Introduction. The second Slovenian national healthcare-associated infections (HAIs) prevalence survey (SNHPS) was conducted in acute-care hospitals in 2011. The objective was to assess the sensitivity and specificity of the method used for the ascertainment of six types of HAIs (bloodstream infections, catheter-associated infections, lower respiratory tract infections, pneumoniae, surgical site infections, and urinary tract infections) in the University Medical Centre Ljubljana (UMCL). Methods. A cross-sectional study was conducted in patients surveyed in the SNHPS in the UMCL using a retrospective medical chart review (RMCR) and European HAIs surveillance definitions. Sensitivity and specificity of the method used in the SNHPS using RMCR as a reference was computed for ascertainment of patients with any of the six selected types of HAIs and for individual types of HAIs. Agreement between the SNHPS and RMCR results was analyzed using Cohen%s kappa coefficient. Results. 1474 of 1742 (84.6%) patients surveyed in the SNHPS were included in RMCR. The sensitivity of the SNHPS method for detecting any of six HAIs was 90% (95% confidence interval (CI): 81%-95%) and specificity 99% (95% CI: 98%-99%). The sensitivity by type of HAI ranged from 63% (lower respiratory tract infections) to 92% (bloodstream infections). Specificity was at least 99% for all types of HAIs. Agreement between the two data collection approaches for HAIs overall was very good (%=0.83). Conclusions. The overall sensitivity of SNHPS collection method for ascertaining HAIs overall was high and the specific
Keywords: bolnišnične okužbe; cross-sectional studies; healthcare-associated infections; občutljivost; okužbe; presečne raziskave; prevalenca; prevalence; retrospective medical chart reviews; sensitivity; Slovenia; Slovenija; specificity; specifičnost